Comparison of the STANDARD M10 C. difficile, Xpert C. difficile, and BD MAX Cdiff assays as confirmatory tests in a two-step algorithm for diagnosing Clostridioides difficile infection - Hyunseul Choi; Minhee Kang; Sun Ae Yun; Hui-Jin Yu; Eunsang Suh; Tae Yeul Kim; Hee Jae Huh; Nam Yong Lee (Microbiology Spectrum)
ABSTRACT Current guidelines recommend a two-step algorithm rather than relying solely on a single test for diagnosing Clostridioides difficile infection. This algorithm starts with enzyme immunoassay (EIA) for detecting glutamate dehydrogenase (GDH) and toxins A/B, followed by nucleic acid amplification test (NAAT) for GDH-positive but toxin-negative cases. This study compared the performance of three commercial NAATs: the STANDARD M10 C. difficile, Xpert C. difficile, and BD MAX Cdiff assays, utilized as confirmatory testing of the two-step algorithm. Two hundred archived stool specimens, previously tested GDH-positive but toxin-negative by EIA, were analyzed in parallel with these NAATs and toxigenic culture, which served as the reference standard. Sensitivity, specificity, positive predictive value, and negative predictive value were 89.1%, 92.6%, 94.6%, and 85.2%, respectively, for the M10 assay; 95.8%, 86.4%, 91.2%, and 93.3%, respectively, for the Xpert assay; and 89.8%, 91.4%, 93.8%, and 86.0%, respectively, for the BD MAX assay. The rates of invalid results were 1.0%, 0.5%, and 1.0% for the M10, Xpert, and BD MAX assays, respectively. In conclusion, the M10 assay is a reliable diagnostic tool, performing comparably to the Xpert and BD MAX assays when used as confirmatory testing in the two-step algorithm.IMPORTANCEWhile numerous studies have assessed nucleic acid amplification tests (NAATs) as stand-alone tests for diagnosing Clostridioides difficile infection, limited research has compared their performance as confirmatory tests in a two-step algorithm. This study evaluated the performance of three commercial NAATs (M10, Xpert, and BD MAX assays) using 200 archived stool specimens initially tested as glutamate dehydrogenase (GDH)-positive but toxin-negative by GDH/toxin A/B enzyme immunoassay, the first step in the two-step algorithm. All three assays demonstrated high sensitivity (89.1% to 95.8%) and specificity (86.4% to 92.6%), with low rates of invalid results (≤1%). Our findings suggest that the M10 assay performs comparably to the Xpert and BD MAX assays when used as confirmatory testing in the two-step algorithm. Offering similar performance and turnaround time to these widely used assays at a slightly lower cost, the M10 assay serves as a practical alternative in this setting.